URBAN EXPANSION AND SUSTAINABILITY OF AQUIFERS: THE CASE OF THE RECHARGE AREA OF THE ARENALES AQUIFER SYSTEM, PROVINCE OF SALTA, ARGENTINA - Zarzoso, Guadalupe S. Vásquez; Rodriguez-Alvarez, María S.; Liendro, Natacha; Sorani, Jazmín; Orué, María Romero; Pérez, Marcela; Iribarnegaray, Martín A. (Geosaberes; Vol 15 (2024), 2024)
Water supply for human consumption in the city of Salta and its metropolitan area depends largely on groundwater. The study was developed in the recharge zone of the Arenales aquifer system, where the settled population depends largely on groundwater for domestic use. The objective was to evaluate the distribution and quality of the water resource through the measurement of water table levels, nitrate content and batteries of 16 control points, as well as the excreta disposal method used in the census homes. All the samples taken presented bacteria content, so, according to the Argentine Food Code, none is considered fit for human consumption. Nitrate concentrations were lower than 45 mg NO 3 - /L considered as the limit for drinking water by the same code. It is concluded that, due to the concentration of nitrates and bacteria, the water presents a fecal-type contamination caused by decentralized excreta disposal wells.